European guidelines for workplace drug testing in urine. Issue 6 (17th April 2017) - Taskinen, Sanna; Beck, Olof; Bosch, Tessa; Brcak, Michaela; Carmichael, Duncan; Fucci, Nadia; George, Claire; Piper, Mark; Salomone, Alberto; Schielen, Wim; Steinmeyer, Stefan; Weinmann, Wolfgang
Abstract : These European Guidelines for Workplace Drug Testing in Urine have been prepared and updated by the European Workplace Drug Testing Society (EWDTS). The first version of these urine guidelines was published in 2002. Since then, the guidelines have been followed by many laboratories in different European countries and their role has been essential particularly in countries lacking legislation for workplace drug testing. In 2014, the EWDTS started a guidelines updating project and published a new version of the urine guidelines in 2015. Here we represent this updated version of the urine guidelines. The European Guidelines are designed to establish best practice procedures whilst allowing individual countries to operate within the requirements of national customs and legislation. The EWDTS recommends that all European laboratories that undertake legally defensible workplace drug testing should use these guidelines as a template for accreditation. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : These guidelines for Legally Defensible Workplace Drug Testing have been prepared and updated by the European Workplace Drug Testing Society (EWDTS). The European Guidelines are designed to establish best practice procedures whilst allowing individual countries to operate within the requirements of national customs and legislation. The EWDTS recommends that all European laboratories that undertake legally defensible workplace drug testing should use these guidelines as a template for accreditation.